John Dewey and the Mind-Body Problem in the Context: The Case of «Neutral Monism» - Leonov, Andrii (Actual Problems of Mind, 2018)
The main focus of this paper is the mind-body problem in its relation to the doctrine of ‘neutral monism’ and the question who can be considered its proponents. According to Bertrand Russell, these are Ernst Mach, William James, and John Dewey (to name a few). This paper aims to clarify whether Russell himself was right in his conclusions or not. At first, I start with the clarification of the relation between ‘neutral monism’ and ‘dual-aspect theory’. Secondly, I analyze the ‘big three’ of the neutral monism: Mach, James and Russell. My starting-point here is Russell’s very understanding of Mach and James positions. In the end, it appears that neither Mach, nor James as well as Dewey can be considered as neutral monists. It was rather Russell’s misunderstanding of the both James’ radical empiricism and Mach’s analysis of sensations, which led him to the creation of his own original version of ‘neutral monism’ (or ‘Russelian monism’).